The village and the class war : anti-kulak campaign in Estonia - Kõll, Anu Mai (Historical studies in Eastern Europe and Eurasia, 2013)
Before collectivization of agriculture in Estonia, "kulaks" (better-off farmers) were persecuted and many of them were finally deported in March 1949. This book is situated on the local level; the aim is to understand what these processes meant from the perspective of the Estonian rural population, a kind of study that has been missing so far. This book analyzes the mechanisms of repression, applying new aspects. Repression was mainly conducted through a bureaucratic process where individual denunciations were not even necessary. The main tool of persecution was a screening of the rural population with the help of records, censuses and local knowledge, in order to identify, or invent, "kulak families." Moreover, in the Estonian sources, the World War II history of each individual was a crucial part of screenings. The prisoners of war of the Red Army, held in camps in Estonia, played an unexpected part in this campaign. Another result is a so-far-neglected wave of peaceful resistance as the kulak identifications were challenged in 1947-48. The results mainly answer the question "how" this process worked, whereas the question "why" finds hypothetical responses in the life trajectories of the actors involved.